2018
DOI: 10.1055/s-0038-1660845
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma for the Treatment of Androgenic Alopecia: A Systematic Review

Abstract: The use of platelet-rich plasma (PRP) has become increasingly commonplace in facial plastic surgery for the treatment of androgenic alopecia (AGA). However, this treatment remains novel with a range of application techniques and outcomes described in the literature. Herein, the authors systematically review the existing literature on the use and efficacy of PRP for AGA. Systematic review of PubMed, Embase, and Cochrane databases was performed. Case reports were excluded. Twenty-four papers met inclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…There were no complications reported other than transient edema/erythema and pain/headache associated with the procedure. PRP is considered a low-risk intervention to treat androgentic alopecia associated with good patient satisfaction and objective improvements in outcomes [6].…”
Section: Discussionmentioning
confidence: 99%
“…There were no complications reported other than transient edema/erythema and pain/headache associated with the procedure. PRP is considered a low-risk intervention to treat androgentic alopecia associated with good patient satisfaction and objective improvements in outcomes [6].…”
Section: Discussionmentioning
confidence: 99%
“…Platelet‐rich plasma treatment has been beneficial in the management of alopecia with reports of significantly increased hair density although lack of clinical improvements has also been reported in some patients. [ 6‐9,17 ] The source of this variability in clinical response could result from heterogeneity in amounts of GFs produced by platelets among patients undergoing PRP treatment. We evaluated GF secretion by activated platelets and provide evidence of variability in their amounts of TGFβ1, PDGF‐BB, EGF, VEGF and FGF2 secretion between patient samples.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we included six additional RCTs not considered by Chen et al Chen et al did not mention that Gentile et al reported the identical data reported by Cervelli et al on 10 people, though this introduced duplicate data bias in favor of PRP. Chen et al concluded that PRP is a favorable low‐risk intervention for pattern hair loss. In concordance with the present review, the authors identified objective improvement of hair density and no serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…One other RCT investigated PRP vs minoxidil, a comparison which did not match the inclusion criteria of the present review. Thus, we included six additional RCTs not considered by Chen et al 49 Chen et al 49 also suggested a good patient satisfaction. In RCTs, we did not find sufficient data on health-related quality of life, likely because we did not include cohort studies.…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%